EU ٍEconomic Sanctions: Legitimacy, Enforcement Mechanisms, and Legal Challenges - Roxana Niknami (دانشنامه حقوق اقتصادی)
Sanctions have become one of the primary foreign policy tools of the European Union, aimed at maintaining international peace, security, and promoting values such as human rights and democracy. However, these measures often face significant legal and enforcement challenges. This article examines the EU’s sanctions framework through the lens of normative power theory, addressing the key research question: "what is the normative legitimacy found of EU sanctions, and how are they enforced both domestically and internationally while managing related legal challenges?" The central hypothesis is that the EU, as a normative power, utilizes sanctions not only as political pressure tools but also as instruments to promote core values such as human rights and democracy. Nevertheless, these sanctions encounter substantial legal challenges on the international stage. The methodology involves legal-normative analysis to assess the legal basis of sanctions within the Common Foreign and Security Policy (CFSP). The findings reveal that while EU sanctions are largely effective in aligning with and promoting international norms, they face significant legal and procedural issues. These include challenges related to the proportionality and human rights impacts of sanctions, inconsistencies in enforcement across member states, and difficulties in achieving compliance with international legal standards. The study concludes that addressing these shortcomings is crucial for enhancing the effectiveness and legitimacy of EU sanctions, and it calls for reforms to better balance strategic objectives with legal and ethical considerations.